The Impact of Drying Temperature and Duration on the Physicochemical and Sensory Properties of Cascara Powder Enriched with Emprit Ginger (Zingiber officinale var. amarum) - Satar, Ibdal; Yuniarti, Adinda; Yusof, Nurhayati; Ahmed, Waled Abdo (Universitas Ahmad Dahlan, 2025)
Cascara, derived from dried coffee pulp, is abundant in polyphenols such as catechin and epicatechin, offering substantial potential for diverse uses. Enriching cascara powder (CP) with emprit ginger (EG) is an ideal innovation, as both are rich in antioxidants, enhancing sensory attributes and health benefits. This study contributed to the effect of different drying temperatures and durations on the physicochemical and sensory properties of CP with and without EG. This study utilized a completely randomized design (CRD) with two factors: drying temperature (45°C, 55°C, and 65 °C) and duration (24, 48, and 72 h). The physicochemical analysis included moisture content, ash content, pH, reducing sugars, total phenolic content, and antioxidant activity of RSA. Sensory evaluation assessed color, taste, and aroma. The results indicated that moisture, ash, pH, reducing sugar, and total phenol contents ranged from 3.82–7.45%, 3.59–10.79%, 4.26–6.51, 14.78–58.51%, and 10.34–50.37 mg GAE/g, respectively. The antioxidant activity of RSA ranged from 45.59% to 87.73%. The sensory tests showed that all formulations were liked by the panelists. Based on physicochemical and sensory properties, the F3t1 formulation with EG was of the best quality. The optimal drying temperature and duration were 45°C and 24 h, with 75% CP and 25% EG (F3t1+J1). This work significantly contributes to the field of food technology by offering valuable insights into the utilization of coffee by-products and the incorporation of bioactive-rich compounds to create innovative, health-focused functional beverages.